Poultry value chain and cluster development in Papua New Guinea: Insights from a recent field study - Fang, Peixun; Gimiseve, Harry; Mukerjee, Rishabh; Schmidt, Emily; Zhang, Xiaobo (International Food Policy Research Institute, 2024)
Despite poultry being lauded as a relatively affordable source of protein and micronutrients in many lower-income countries, chicken meat is twice as expensive in PNG compared to nearby Southeast Asian countries. Recent rural household consumption data collected by the International Food Policy Research Institute (IFPRI) suggests that an important share of households do not eat enough protein to meet healthy dietary guidelines (Schmidt et al., 2024). Poultry, along with fish and pork, are the three most important animal-source protein foods in the country, yet these products remain financially prohibitive to a large share of the population.